Physa acuta Draparnaud, 1805 (Gastropoda: Physidae): a study of topotypic specimens - W Lobato Paraense; Jean-Pierre Pointier (Memorias do Instituto Oswaldo Cruz, 2003)
A description is given of Physa acuta Draparnaud, 1805, based on topotypic specimens from the Garonne river basin, and additional samples from the environs of the French cities of Montpellier and Perpignan. It proved indistinguishable, in shell and anatomy, from topotypic Physa cubensis Pfeiffer, 1839, thus leading the authors to admit the synonymy of the two nominal species under the older name, P. acuta.